The Pro-Life Pregnancy Help Movement : Serving Women or Saving Babies? - Hussey, Laura S. (Book collections on Project MUSE., 2019)
"The American pro-life movement is known primarily for its picketing of abortion clinics and its lobbying on behalf of government policies designed to make abortion more difficult to obtain or even illegal altogether. But in addition to this highly public side to pro-life activism, there is the less well-known work of direct service to pregnant or parenting women through a network of "pregnancy centers" that activists call "the pregnancy help movement." The growth of this movement suggests that pro-life activists may be trying to accomplish through nongovernmental venues what they are unable or unwilling to accomplish through public policy advocacy. Academic research on these pregnancy centers has been highly limited, and Laura Hussey's work presents the most extensive social-scientific study to date of a common but little-known and sometimes controversial form of pro-life activism. Drawing on a wealth of original data on organizations, individual activists, and their political and social contexts, the book revises and expands scholarly and popular portrayals of anti-abortion activism"--